Clinical psychologists and the demands concerning parental disputes - Martins de Sousa, Analicia (2021)
Clinical psychologists are increasingly sought after by parents involved in child custody lawsuits, with allegations of parental alienation and / or child sexual abuse. In these situations, requests for psychological documents are common, which are invariably forwarded to justice. In addition to increasing procedural action, such documents have resulted in ethical complaints in the category councils, made by parents who feel demmage by its content. This essay aims to contribute from the theoretical, technical and ethical point of view of Psychology to discussions about documents produced by psychologists who work as clinical psychologists. Allied to the experience of the authors as forensic psychologists, is adopted the social critical approach. We note that the reduced involvement of those (s) professionals in the debates on post-divorce family makes practices in the area easy to reach of judicialization. Thus, we point out that the interdisciplinary dialogue is urgent and essential.